2009
DOI: 10.1111/j.1445-2197.2009.05103.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results after excision of breast mass using a vacuum‐assisted biopsy device

Abstract: Ultrasound-guided VABD excision is a minimally invasive technique for the complete removal of benign breast tumours. The results of this long-term follow-up of VABD excisions are comparable to conventional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 14 publications
(21 reference statements)
1
22
0
3
Order By: Relevance
“…In 141 patients, more than 10 frustules were taken in an attempt to completely remove the lesion using VABB with an 11- or 8-gauge probe, but complete removal occurred only in 93 cases, while in the remaining 48 cases, after the ultrasound-guided follow-up 6 months later, minimum residue of the lesion was still present [17, 18, 19, 20]. …”
Section: Resultsmentioning
confidence: 99%
“…In 141 patients, more than 10 frustules were taken in an attempt to completely remove the lesion using VABB with an 11- or 8-gauge probe, but complete removal occurred only in 93 cases, while in the remaining 48 cases, after the ultrasound-guided follow-up 6 months later, minimum residue of the lesion was still present [17, 18, 19, 20]. …”
Section: Resultsmentioning
confidence: 99%
“…In agreement with our results Yom et al found that residual benign tumour was more seldom the later follow-up ultrasound was performed: when follow-up was within 2 years of the procedure residual tumour was found in 10 % of cases and scar tissue in 36 %. Beyond 2 years these figures were only 6.5 and 15.8 % respectively [23]. The early follow-up in our study collective possibly explains the relatively high rate of suspected residual tumour.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast to surgical excision it can be performed under local anaesthesia and leaves neither cosmetic impairment nor problematic breast tissue scars [6,8,15,23].…”
Section: Introductionmentioning
confidence: 99%
“…Неполное удаление патологического образования путем ВАБ впоследствии диагностируется в виде оста-точных изменений (масс) в 10-38 % случаев [13,16,34,50], причем размер зонда (иглы), используемого для ВАБ, не влияет на наличие остаточных изменений и их частоту, однако случаи с остаточными поражени-ями имеют место при удалении образований размером >1 см [12,13]. Удаление образований большого разме-ра или расположенных вблизи соска, удаление сразу нескольких очагов чаще сопровождались наличием остаточных изменений [12].…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified
“…[39], все фиброаденомы размером >2 см не были полностью удалены при ВАБ, фибро-аденомы размером 1,5-2,0 см были полностью удале-ны только в 55 % случаев, а полное удаление было достигнуто при всех поражениях размером до 1,5 см (при среднем объеме 0,25 мл). Остаточные массы по-сле ВАБ почти в 2 раза реже наблюдались при оценке спустя 2 года [50].…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified